A Social Justice Theory of Active Equality for Technical Communication. (January 2018) - Colton, Jared S.; Holmes, Steve
Certain aspects of social justice research tacitly work from political frameworks of "passive equality." Passive equality can limit a technical communicator's ability to enact social justice in terms of (a) signaling the presence of an injustice and (b) waiting for the organization, institution, or state to make the correction (e.g., liberalism's distributive justice). By contrast, this article foregrounds the political philosophy of Jacques Rancière as a way to cultivate a practice of "active equality" that enables technical communicators to enact social justice rather than wait for institutional redistribution.